Conservation Status and Agroforestry Opportunity of Commercially Important Medicinal Plants of Himachal Pradesh - Negi, Satya Prakash (Indian Forester, 2018)
Himachal Pradesh situated in Indian Himalayan Region is known for a rich floral and faunal diversity. The floral diversity of the state is famous for their medicinal value as local inhabitants have been traditionally using them for herbal remedies since ancient times. There are important medicinal plants which have high commercial worth and the locals have been harvesting them usually from the forests for trade so as to augment their revenue. The traders pay the prescribed permit fee to the Forest Department for trading these commercially important medicinal plants. However, unmanaged and destructive harvesting of these medicinal plants is putting tremendous pressure on forests, as forests are the primary source of these plants. Assessment of conservation status of these commercially important medicinal plants is important in order to safeguard them for continued benefits of these important plant species for human wellbeing. The global demand for medicinal plants will continue to rise and the best alternative to bridge the growing demand of commerce is cultivation that will not only help in in-situ conservation but also ensure continued supply of medicinal plants for our herbal medicinal requirements. Agroforestry offers a tremendous opportunity of producing many of these commercially important medicinal plants that will supplement income to the farmers in addition to the traditional crops grown on their farm. This paper discusses the medicinal species of commercially important plants with their status in Himachal Pradesh and opportunity to grow them in different agroforestry systems in the state.